Active transportation policy and practice in the city of Oulu from 1998 to 2016—A mixed methods study - Mikko Kärmeniemi; Tiina Lankila; Emilia Rönkkö; Kari Nykänen; Heli Koivumaa-Honkanen; Raija Korpelainen (Journal of Transport and Land Use)
Land use and transportation policies have been recognized globally as major sources of physical inactivity, but there has been a gap between research and policy implementation. Our objective for this research was to produce an integrated view of community planning policies and the association between urban form characteristics and transportation mode choices in the city of Oulu from 1998 to 2016.